Synthesis of gold nanoparticles via block copolymer template and their application in organic solar cells - Nguyen, Thi Minh Hieu. (2011)
Recently, great efforts have been put in to improve the efficiency of organic solar cell. One of the directions that has attracted attention, involves the utilization of surface plasmons in metal nanoparticles to enhance the photoactive absorption and photocurrent. However, the nanoparticles patterns in these studies are usually scattered and random, which make it difficult to systematically examine the surface plasmon effect on cell performance. Hence, by applying the block copolymer (BCP) PS-b-P4VP as a template to synthesize dense, ordered and controlled nanoparticles patterns in organic photovoltaics, the surface plasmon effect on the device performance can be systematically studied. Upon integrating the gold nanoparticles (Au NPs) of size 20nm and 14nm in P3HT:PCBM cell, it was found that the short circuit current densities are increased by 31% and 39% respectively. This enhancement is explained due to the surface plasmons of Au NPs that can confine light to the metal/dielectric interface, which in turn generates intense local electromagnetic fields and greatly amplifies absorption in nearby photoactive materials. This speculation is verified by UV-Vis spectrum that shows significant enhancement in absorption of P3HT: PCBM photoactive layer in the vicinity of Au NPs. In Au NPs integrated devices, the incident photon to current efficiency (IPCE) enhancement (%) is observed in the entire visible range and more pronounced at 590nm. Besides, it is also observed that 14nm Au NPs contribute to greater improvement in cell performance than 20nm Au NPs. The block co-polymer approach offers the synthesis of ordered metal nanoparticles not only with varying sizes, but also with varying interparticle spacing via block length alteration.